"A stitch in time": group work during the covid-19 scare in the Nicobar Islands, India. Issue 1 (2nd January 2021) - Saini, Ajay
ABSTRACT: When India suddenly went into its first coronavirus-induced nationwide lockdown in March 2020, several members of a historically isolated indigenous community in the eastern Indian ocean- the Nicobarese, began to panic. Their leaders came together and formed a group to boost community solidarity and helped the vulnerable indigenes to safely navigate through the crisis. In these uncertain times of Covid-19, when the "modern" world appears more fissured than ever, leaving its "others" to fend for themselves; the Nicobarese's group has set an example for everyone to follow.